Evaluating the influence of a medical journal using Google Scholar - Sanni, S.A.; Zainab, A.N. (2011)
This study shows how a journal's influence can be calculated by using citations obtained from Google Scholar and other methods even though the journal is not covered by any citation databases. Influence is measured in terms of foreign contributions, 'equivalent' immediacy scores of recent articles, and the calculation of citations and 'equivalent' impact factor. A total of 580 articles published in the Medical Journal of Malaysia (KM) between 2004 and 2008 served as the sample. Very few foreign authors contributed to MJM (12.5), implying its low regional acceptance as a channel for research communication. Immediacy scores for each year indicate citations were received by recently published articles. A total of 1,164 citations were received by 446 of the 580 articles and the main citing sources were journals (1,083) with reasonable is index and impact factor. Yearly impact scores ranged between 0.367 and 0.616. Higher impact factor scores were obtained by older articles. (C) S.A. Sanni and A.N. Zainab 2011